Hazard level of vehicle smoke by fuzzy multiple attribute decision making with simple additive weighting method - Abadi S.; Huda M.; Teh K.S.M.; Haroon Z.; Ripin M.N.; Hehsan A.; Sarip S.; Hehsan M.R.; Amrullah M.; Maseleno A. (Advanced Scientific Research, 2024)
Indexed by Scopus